ئەنجومەنی ئاوەدانکردنەوە لە عێراق و لێکەوتە ئابوورییەکانی (١٩٥٠–١٩٥٨) ژێرعنوان: - مصطفى, ڕێبوار خالد (Sulaimani Journal for Humanities, 2021)
Iraq is a reach country on natural resources, after establishment of Iraq in (1921), did not useful on natural resources for developing in construction and built up, that was impact on political, economic and social circumstances. For treatment of these circumstances on the recommendation of economist’s specialists, the Iraqi government had established buildup board in (1950), the purpose of this board were foundation new projects, developing economy, general service and increase life style in Iraq. The goals of these projects had starting by a new program and planning in the fields of the strategic projects on agriculture irrigation, factors, oil refining, industrial factors and general road services had done. All these projects that have done by the board of buildup had a positive effect on the future of Iraqi economic and factors for developed of construction and infrastructure in Iraq. On behind of these developing in the most sectors, rather than the board got of many difficulty and economic, political problems and refused by the population of Iraq. That is factoring of dissolution it, after July (1958) coup in Iraq. This paper depends of many methods that suitable with this topic to indication factors and goals of establishing of the buildup board in Iraq with the effect of these projects that have done by these board and subsequent these projects in Iraq.